Dioxin Perspectives A Pilot Study on International Information Exchange on Dioxins and Related Compounds - Bretthauer, Erich W.; Kraus, Heinrich W.; Domenico, Alessandro di (Nato Challenges of Modern Society, 1991)
Erich W. Bretthauer, Chairman of the Exposure and Hazard Assessment Working Group U. s. Environmental Protection Agency Washington, D. C. The efforts of the Exposure and Hazard Assessment Working Group were focused on the exchange of information on a variety of topics including research projects, regulations/statutes, analytical laboratories, and methods of exposure/risk assessment involving CDDs and CDFs. It was evident to the leaders of the Working Group that several of the knowledge voids had to be addressed on a fundamental level before expanded efforts could be made. Several questions needed to be answered: ? Who has done research on this topic, and what do the data indicate? ? Who is performing research now, and what are their capabilities? ? How are other nations addressing this problem, and do they have legislative mandates in place? ? Is there a general consensus on the topic? The members of the Working Group believed that these questions could be answered by surveying the major participants in the field of interest. Three principal survey efforts were performed by the Working Group, which collected information on research, regulations/statutes, and analytical laboratories from each of the participating nations. In addition to answering these fundamental questions, these efforts also fulfilled the major objectives of the entire Pilot Study. The collection, analysis, and distribution of information on research projects, regulations/statutes, and analytical laboratories were very useful efforts in helping to fill some of the basic knowledge voids